Technology and Inequalities in Education – A case of Massive Open Online Courses (MOOCs) in Distance Education in India as a means of Exclusion - Naithani, Arunima (H. : ĐHKT, 2020)
The Open and Distance Learning in India (or distance education) plays a significant role in democratising the higher education system of the country. The growth and development of distance education, as a sub-system of higher education in India has experienced several stages. Beginning from pure correspondence courses in early 1960s, the range of educational programmes, and institutional access has evolved and developed over time into technology-enabled education system. Today, there are 14 State Open Universities, Indira Gandhi National Open University –IGNOU, in addition over 40 Universities (Private, central, state) which are dual mode institutions to provide distance education academic courses. In terms of enrollment of students, distance education courses constituted 11.05 per cent of the total gross enrollment ratio (GER) of 26 per cent in higher education, especially at the UG, PG, and Certificate levels courses (AISHE Report, 2017-18). Impressively, the national open university of India – IGNOU offers 232 academic programs and is the world's largest university in terms of ever-growing enrolment (IGNOU Prospectus, 2017-18). This indicates a progressive trend in distance education system in India as more than 3 million students are enrolled in various distance-learning programmes offered by such institutes (Gaba & Li, 2015).